Arsenic trioxide and Erlotinib loaded in RGD‐modified nanoliposomes for targeted combination delivery to PC3 and PANC‐1 cell lines. (21st September 2022) - Khosravani, Fatemeh; Mir, Hamed; Mirzaei, Ali; Kobarfard, Farzad; Bardania, Hassan; Hosseini, Ebrahim
Abstract: During the past few years, advances in drag delivery have provided many opportunities in the treatment of various diseases and cancer. Arsenic trioxide (ATO) and Erlotinib (Erlo) are two drugs, approved by the United States Food and Drug Administration to treat cancer, but their use is limited in terms of the toxicity of ATO and the low solubility of Erlo. This study aimed to prepare arginine‐glycine‐aspartic acid (RGD)‐decorated nanoliposomes (NLPs) containing Erlo and ATO (NLPs–ATO–Erlo–RGD) to increase the solubility and reduce the toxicity of Erlo and ATO for cancer treatment. The results of transmission electron microscopy and dynamic light scattering showed that NLPs were synthesized uniformly, with spherical shape morphology and particle sizes between 140 and 160 nm. High‐performance liquid chromatography and ICP–MS results showed that about 90% of the drug was loaded in the NLPs. In comparison with NLPs–ATO–Erlo, NLPs–ATO–Erlo–RGD demonstrated considerable toxicity against the αvβ3 overexpressing PC3 cell line in the MTT experiment. It had no effect on the PANC‐1 cell line. In addition, apoptosis assays using Annexin V/PI demonstrated that NLPs–ATO–Erlo–RGD generated the highest apoptotic rates in PC3 cells when compared with NLPs–ATO–Erlo and the combination of free ATO and Erlo. Furthermore, treatment with NLPs–ATO–Erlo–RGD in ( p < 0.05) PC3 cell line significantly reduced EGFR level. It is concluded NLPs–ATO–Erlo–RGD as a novel drug delivery system may be a promising platform for the treatment of cancer.